Understanding Mental Health Stigma: A Global Qualitative Perspective - Yusup, Aldian (Raudhah Publisher, 2024)
Understanding mental health stigma is essential to addressing global health inequalities. This study uses a qualitative approach through literature review and library research to examine various dimensions of mental health stigma in various cultural contexts. By synthesizing findings from various qualitative studies, we aim to uncover common themes and unique cultural factors that influence stigma against mental health. Our analysis reveals that stigma is widespread and appears in a variety of ways, significantly influencing individuals' desire to seek help and comply with treatment. Factors such as cultural beliefs, social norms, and lack of education contribute to the sustainability of stigma. In addition, the role of media and language in shaping perceptions of mental illness is also explored. The study highlights the need for culturally sensitive interventions and policies that address the root causes of stigma. These findings suggest that global efforts to reduce mental health stigma should consider cultural specifics and involve community-based strategies to encourage acceptance and support for individuals with mental health conditions. Further research should focus on the development and evaluation of such interventions to ensure their effectiveness in a variety of cultural settings. By broadening our understanding of mental health stigma from a global perspective, this study contributes to a broader discourse on mental health equity and the development of more inclusive health policies.